2002
DOI: 10.4049/jimmunol.168.4.1950
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of MHC Class I Molecules by Tapasin into the Transporter Associated with Antigen Processing-Associated Complex Is Essential for Optimal Peptide Loading

Abstract: The ER protein tapasin (Tpn) forms a bridge between MHC class I H chain (HC)/β2-microglobulin and the TAP peptide transporter. The function of this TAP-associated complex was unclear because it was reported that soluble Tpn that has lost TAP interaction would be fully competent in terms of peptide loading and Ag presentation. We found, however, that only wild-type human Tpn (hTpn), but not three soluble hTpn variants, a transmembrane domain point mutant of hTpn (L410→F), wild-type mouse Tpn, nor a mouse-human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
140
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 64 publications
7
140
3
1
Order By: Relevance
“…First, it stabilizes TAP as TAP expression is drastically decreased in tapasin-deficient cells [5,25,51,75]. Second, by MHC class I binding and recruitment of ERp57 [19,71], tapasin coordinates and facilitates peptide loading of MHC class I molecules [50,62,83,92,102]. Tapasin-deficient mice show an impaired immune response and an altered peptide repertoire presented on MHC class I molecules [24].…”
Section: Tap Is the Key Component Of The Mhc Class I Peptide-loading mentioning
confidence: 99%
“…First, it stabilizes TAP as TAP expression is drastically decreased in tapasin-deficient cells [5,25,51,75]. Second, by MHC class I binding and recruitment of ERp57 [19,71], tapasin coordinates and facilitates peptide loading of MHC class I molecules [50,62,83,92,102]. Tapasin-deficient mice show an impaired immune response and an altered peptide repertoire presented on MHC class I molecules [24].…”
Section: Tap Is the Key Component Of The Mhc Class I Peptide-loading mentioning
confidence: 99%
“…13 It also enhances the rate and extent of class I MHC loading with optimal peptides. [14][15][16][17] In tapasin-deficient cells, the repertoire of class I-bound peptide is thus skewed towards less stably binding ones, a phenomenon that is consistent with the phenotype of C57BL/6 mice that lack tapasin and B2705 expressed in 0.220. [18][19][20] Tapasin is a type I transmembrane glycoprotein with a dilysine ER-retention motif (KxKxx) in its cytoplasmic tail.…”
Section: Introductionmentioning
confidence: 59%
“…Weak co-IP of TPSN Ex3 by ERp57 was albeit found, indicating that an indirect interaction via other PLC components might occur (discussed later). Similarly, calreticulin was found to co-precipitate TPSN Ex3 although to a lesser extent than tpn.Previous studies have shown that the TMSs confer the interaction between TAP and tpn [6,8,9]; therefore, as expected, binding to TAP was not affected by deletion of exon 3. Interestingly however, we detected a weak but reproducible interaction between TPSN Ex3 and MHC-I.…”
mentioning
confidence: 66%
“…Proper peptide loading of MHC-I is controlled by several chaperones that form the peptide loading complex (PLC) in the ER [4]. In the PLC the MHC-I heterodimer associates with tapasin (tpn), calreticulin, ERp57, and indirectly with TAP; tpn and TAP interact via their transmembrane segments (TMSs), thereby stabilizing the structure and function of TAP [5][6][7][8][9]. It has been shown that both TAP1 and TAP2 subunits possess binding sites for tpn at their N-terminal TMSs [10][11][12].…”
mentioning
confidence: 99%